Missing Part in Adjustable Pressure Limiting Valve in Bain’s Circuit: A Near Miss - Divya Devanathan (Case Reports in Clinical Practice, 2023)
Breathing circuits are the delivery systems which conduct anaesthetic gases from an anaesthetic machine to the patient. They are designed for either spontaneous respiration or intermittent positive pressure ventilation (IPPV). The Bain co-axial circuit, a modification of Mapleson D system is the most commonly used circuit in outside operating room procedures. It has several advantages over the circle system in that it is light-weight, convenient with adjustable length. Although most problems with the circuit involve disconnections, obstruction problems related to kinks in the gas delivery tube  or foreign body in the elbow have been reported. We would like to report an anaesthetic incident involving desaturation of patient posted for electro convulsive therapy (ECT) due to missing part of the Adjustable Pressure Limiting (APL) valve.